Clostridioides difficile-induced diarrhoea following dasatinib therapy - Datta, Amlan Kusum (BMJ Case Rep, 2021)
Dasatinib, an oral tyrosine kinase inhibitor, is approved for therapy of chronic myeloid leukaemia (CML). Common adverse effects of this therapy include myelosuppression, fluid retention and diarrhoea. However, Clostridioides difficile infections (CDIs) in the context of dasatinib therapy, without a history of antecedent antibiotic use, has not been reported previously. We present here a case of a 36-year-old man diagnosed with accelerated phase of CML, who was started on treatment with dasatinib. Two months into therapy, he experienced profuse diarrhoea and abdominal pain. Colonoscopy revealed multiple confluent colonic mucosal ulcerations. Immunoassay study of stool revealed positive C. difficile toxin. The patient was started on oral metronidazole, with discontinuation of all other drugs, including dasatinib. He made a complete uneventful recovery following 2 weeks of antibiotic therapy. Chemotherapeutic agents, such as dasatinib, should be considered as possible etiological agents in the pathogenesis of CDI, even in absence of antibiotic use.